Clinical features and treatment of drug fever caused by anti‐tuberculosis drugs. (29th December 2014) - Fang, Yong; Xiao, Heping; Tang, Shenjie; Liang, Li; Sha, Wei; Fang, Yuanyuan
Abstract: Background and Aims: Tuberculosis is a major global health problem. However, anti‐tuberculosis drug treatment has many adverse effects, such as drug‐caused fever. The aim of this study was to investigate the clinical features and treatments of anti‐tuberculosis drugs‐induced fever. Methods: A total of 78 inpatients and outpatients with pulmonary tuberculosis accompanied by drug fever during the anti‐tuberculosis treatment were analysed retrospectively from April 2006 to March 2013. Results: Among the anti‐tuberculosis drugs that caused the drug fever, rifampicin was the most common one, followed by para‐aminosalicylic and pyrazinamide. The symptoms occurred within 2 months after treatment, mainly in the 1–3 weeks, and the main symptom was high fever with body temperature above 39°C. The accompanying symptoms include rash, chills, headache, stuffy nose, runny nose, nausea, vomiting and joint pain. Routine blood examination found that eosinophilia increased in 15 cases and decreased in another 15. Among 63 patients who underwent liver function tests, there were 10 cases of abnormal function and 4 cases of liver damage. When the drug fever was suspected, the measure of withdrawal was taken first. All the suspected drugs were withdrawn in 59 cases, while gradual withdrawal was conducted in 19 cases. Patients with complications were first treated in accordance with the principles of complications treatment and then were gradually given some drugs after recovery. The patients without complications were gradually given some drugs after the body temperature was back to normal. Conclusion: Drug fever is an allergic reaction, the resolution of which depends on whether it was accompanied by liver damage and/or rash or not.